Neonatal Respiratory Failure Caused by Congenital Diffuse Intrinsic Pontine Glioma. (May 2017) - Satrom, Katie M.; Phelan, Rachel A.; Moertel, Christopher L.; Brent Clark, H.; Johnson, Dana E.; George, Thomas N.
The authors present a case of diffuse intrinsic pontine glioma presenting in a newborn with stridor and respiratory distress that progressed to respiratory failure. Magnetic resonance imaging (MRI) of the brain revealed findings compatible with the diagnosis of diffuse intrinsic pontine glioma. The family pursued palliative care and postmortem examination confirmed WHO grade III astrocytoma.